Impact of structural changes on bank competition in dual banking industry - Nafisah Mohammed,; Junaina Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The banking industry in Malaysia has undergone a change in its market structure, especially in terms of competition due to several factors such as the implementation of the merger program, restructuring of the Islamic banking operations, liberalization and technological advancement. Therefore, this study is conducted to measure the changes in the degree of competition in the Malaysian dual banking due to structural changes occurring in the industry. The Panzar-Rosse (PR) method has been used to measure the degree of competition in the Malaysian dual banking market for the period 1997-2016. Present study uses static panel data estimation to estimate the developed models. The value of H-statistics indicates that Islamic and conventional banks operate in monopolistic competition market structure. The findings show that structural changes have increased the level of competition in the Malaysian banking industry. The results of the study show that policy changes made by Bank Negara Malaysia have improved the level of competition in the Islamic and conventional banking markets. Knowledge of competitive issues is crucial so that policy makers may formulate new policies for the banking industry that suit the current market structure.